2015
DOI: 10.3390/antiox4010204
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin as a Natural Antioxidant: An Overview of the Current Evidence and Perspectives

Abstract: Silymarin (SM), an extract from the Silybum marianum (milk thistle) plant containing various flavonolignans (with silybin being the major one), has received a tremendous amount of attention over the last decade as a herbal remedy for liver treatment. In many cases, the antioxidant properties of SM are considered to be responsible for its protective actions. Possible antioxidant mechanisms of SM are evaluated in this review. (1) Direct scavenging free radicals and chelating free Fe and Cu are mainly effective i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
362
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(388 citation statements)
references
References 274 publications
(335 reference statements)
17
362
2
7
Order By: Relevance
“…There are many possible mechanisms by which silymarin can improve the antioxidant defense mechanisms and oxidative status. Recent studies revealed that silymarin can scavenge free radicals in the gut, prevent the formation of free radicals by inhibiting specific ROS-producing enzymes and improve the integrity of electron-transport chain of mitochondria in stress conditions (Gabrielova et al, 2015;Surai, 2015;Feng et al, 2016). Silymarin was also shown to maintain an optimal redox balance in cells by activating a range of antioxidant enzymes and non-enzymatic antioxidants via the activation of specific transcription factors (Zhao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many possible mechanisms by which silymarin can improve the antioxidant defense mechanisms and oxidative status. Recent studies revealed that silymarin can scavenge free radicals in the gut, prevent the formation of free radicals by inhibiting specific ROS-producing enzymes and improve the integrity of electron-transport chain of mitochondria in stress conditions (Gabrielova et al, 2015;Surai, 2015;Feng et al, 2016). Silymarin was also shown to maintain an optimal redox balance in cells by activating a range of antioxidant enzymes and non-enzymatic antioxidants via the activation of specific transcription factors (Zhao et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, due to their localization, mitochondrial enzymes are particularly vulnerable to ROS, leading to mitochondrial dysfunction and increases in oxidative pressure during critical reproductive periods in sows (Lapointe, 2014). There are many possible mechanisms by which silymarin can improve the antioxidant defense mechanisms and oxidative status (Gabrielova et al, 2015;Surai, 2015;Feng et al, 2016), and its beneficial effect in protecting against systemic oxidative stress was recently demonstrated in late-pregnant sows . It is likely that the dose of silymarin needed to elicit antioxidant effects is lower than that required to stimulate milk yield.…”
Section: Introductionmentioning
confidence: 99%
“…MT decreases the formation of free radicals, inhibits lipid peroxidation, and acts as an antioxidant. Furthermore, MT exerts antifibrotic effects by inhibiting the binding of toxic agents to membrane receptors of hepatocytes (5,6). It was reported that treatment with silymarin (400 mg/d) in combination with UDCA (450 mg/d) provided an enhanced improvement in the hepatic functions of 30 patients with chronic ethylic hepatopathy (7).…”
Section: Introductionmentioning
confidence: 99%
“…and vitagene activation and synthesis and increased expression of protective molecules (GSH, thioredoxins, SOD, heat shock proteins, sirtuins, etc.). Indeed, elucidating roles of vitagenes in stress resistance of poultry as a background for the development of effective strategies to deal with stresses is an emerging topic of research [1][2][3][4][5]. It is known that adaptive SOD synthesis is under vitagene control.…”
Section: Introductionmentioning
confidence: 99%